The location and structure of double-strand DNA breaks induced during yeast meiosis: evidence for a covalently linked DNA-protein intermediate. - Liu, J (1995)
We have determined the precise location and structure of the double-strand DNA breaks (DSBs) formed during Saccharomyces cerevisiae meiosis. Breaks were examined at two recombination hot spots in both wild-type and rad50S mutant cells. At both loci, breaks occurred at multiple, irregularly spaced sites in a approximately 150 nucleotide interval contained within an area of nuclease-hypersensitive chromatin. No consensus sequence could be discerned at or around break sites. Patterns of cleavage observed on individual strands indicated that breaks initially form with a two nucleotide 5' overhang. Broken strands from rad50S mutant cells contained tightly bound protein at their 5' ends. We suggest that, in S.cerevisiae, meiotic recombination is initiated by a DSB-forming activity that creates a covalently linked protein-DNA intermediate.